2013
DOI: 10.12659/msm.889362
|View full text |Cite
|
Sign up to set email alerts
|

Resistance circuit training reduced inflammatory cytokines in a cohort of male adults with Down syndrome

Abstract: BackgroundIt is widely accepted that muscle strength plays a key role on functional tasks of daily living and employability in individuals with Down syndrome (DS). Recent studies have also reported resistance training may improve chronic inflammation in other clinical situations. This is the first study conducted to determine the effect of resistance circuit training on low-grade systemic inflammation in adults with DS.Material/MethodsA total of 40 young male adults with DS were recruited for the trial through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…For this reason, the pronounced increase in body fat (Bertoli et al, 2006; Yamaki, 2005), and the adolescents with intellectual disability who are overweight or obese also present an elevated number of obesity-related secondary conditions such as high blood pressure, high blood cholesterol, diabetes, fatigue 10 compared to peers of a healthy weight (Rimmer et al, 2010). These results are consistent with studies which examine the effect of body fat following CE in Down syndrome (Rosety-Rodriguez et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
“…For this reason, the pronounced increase in body fat (Bertoli et al, 2006; Yamaki, 2005), and the adolescents with intellectual disability who are overweight or obese also present an elevated number of obesity-related secondary conditions such as high blood pressure, high blood cholesterol, diabetes, fatigue 10 compared to peers of a healthy weight (Rimmer et al, 2010). These results are consistent with studies which examine the effect of body fat following CE in Down syndrome (Rosety-Rodriguez et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
“…Dieli-Conwright et al shown that leptin, adiponectin, and body mass index were signi cantly improved after 16 weeks of aerobic and resistance exercise in overweight or obese survivors of breast cancer [25]. Rosety-Rodriguez et al reported that leptin level was signi cantly decreased after the completion of the resistance circuit training [26]. Above previous studies, regular resistance exercise improved leptin and adiponectin levels in both groups with decrease of body fat percentage.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, RT has received much less attention on this topic. Not only in studies focused on disabled people [ 12 ] but also on general population, in spite of published results were promising [ 27 , 28 ]. In this respect, Gambassi et al [ 27 ] found that an 8-week dynamic resistance training protocol improved oxidative damage in stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons already mentioned may contribute, at least in part, to hinder health-care providers to encourage RT for people with DS. Fortunately, in a previous study, our research group reported resistance training was safe and effective in order to reduce systemic low-grade inflammation in adults with DS [ 12 ] and without DS [ 13 ].…”
Section: Introductionmentioning
confidence: 99%